THE NECESSITY AND POSSIBILITIES OF A HERMENEUTICAL ATTITUDE IN CONTEMPORARY PHILOSOPHICAL CULTURE - Károly VERESS (Studia Universitatis Babeș-Bolyai. Philosophia)
The Necessity and Possibilities of the Hermeneutical Attitude in Contemporary Philosophical Culture. Philosophical preoccupations (as the scientific research of philosophy, its creative cultivation, and the process of philosophical training) are confronted nowadays with rapid changes in existential circumstances, the radical restructuring of the social, political, and cultural context, and the challenges of new experiences. Contemporary society and culture show signs of a comprehensive change of perspective and attitude, and for the active participation in this change, a “living”, efficient, and practical philosophy is needed. However, in order to achieve this participation, philosophical preoccupations themselves also have to go through a change of perspective and attitude. In this spirit, I investigate the conditions under which the subject-centred research on philosophy and the cultivation of philosophy can give place to philosophizing according to dialogical principles, and the possibilities, chances, and obstacles of the hermeneutical attitude in the institution-building processes, organisation of activities, and communication related to philosophy.